DETERMINATION OF BORAX IN WET NOODLE IN SEPATAN MARKET TANGERANG BY TURMERIC INDICATOR PAPER, FLAME TEST, AND UV-VIS SPECTROPHOTOMETRY - Rulyta Aulia Munandar; Nita Rusdiana; La Ode Akbar Rasydy (Universitas Muhammadiyah Magelang, 2022)
Borax is a dangerous material if it is contained in food so its use is prohibited. Borax contained in wet noodles is used as a preservative to keep the noodles supple and durable. There are reports in several areas in Tangerang about the content of borax in food, but no research has been conducted in the Sepatan Market, Tangerang Regency. Identification of borax by qualitative test using flame test method and curcumin paper color test, while quantitative test using UV-Vis Spectrophotometry method with a wavelength of 536.40 nm. Two of the total samples tested using ultraviolet visible spectrophotometric instruments showed negative borax content when compared to the flame test and curcumin paper color test. Wet noodle samples sold at Pasar Sepatan, Tangerang Regency, showed a positive content of Borax at 85.71% of the total sample.